RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES (The journal of theological studies, 1928)
RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES, The Journal of Theological Studies, Volume os-XXX, Issue October, 1 October 1928, Pages 110–112, https://doi